Capital gains tax reform - Stuart Adam; Arun Advani; Helen Miller; Andy Summers (Institute for Fiscal Studies (IFS), 2024)
Should the government raise capital gains tax in the Budget? What is the case for reforming capital gains tax? What are the options for reform?
Keywords: 330; Business and investment; Taxes and benefits; Income taxes; Investment; Savings; Tax; Taxes on wealth and spending; Wealth